Systematics, evolution and biogeography of the Southern African burrowing scorpions, Opistophthalmus C.L. Koch (Scorpiones, Scorpionidae) - Prendini, Lorenzo (Department of Biological Sciences, 2014)
Bibliography: p. [597]-643.